Modulation of band bending of gallium arsenide with oriented helical peptide monolayers - Kaindl, Thomas; Adlkofer, Klaus; Morita, Tomoyuki; Umemura, Junzo; Konovalov, Oleg; Kimura, Shunsaku; Tanaka, Motomu (The journal of physical chemistry. C, Energy, materials, and catalysis, 2010)
We propose a strategy to modulate the electronic structure of gallium arsenide (GaAs) semiconductors by the covalent deposition of uniform monolayers of helical peptides. After the optimization of coupling groups and reaction conditions, structures of peptide monolayers on GaAs were characterized by the combination of grazing incidence-X-ray scattering and Fourier transform infrared spectroscopy yielding the thickness, the area occupied by one peptide helix, and the tilt angle of helical axis with respect to the surface normal. The deposition of the same peptides on high electron mobility transistor (HEMT) devices resulted in a clear change in the carrier mobility depending on the length of peptide helices. The obtained results demonstrated that the macrodipole potential of oriented peptide helices can be utilized for flexible tuning of the electronic structure (band bending) of semiconductors, which can offer a unique alternative to the commonly used doping of charge carriers.